Complex pediatric neoplasms: The role of congenital cardiothoracic surgeryCentral MessagePerspective - Lindsay J. Nitsche, BS; Colleen E. Bontrager, BA; Paul J. Devlin, MD; Lea F. Surrey, MD; Jennifer E. Pogoriler, MD, PhD; Portia A. Kreiger, MD; Theodore W. Laetsch, MD; Frank Balis, MD; Alexander S. Fairman, MD; Peter Mattei, MD; Stephanie M. Fuller, MD, MS (JTCVS Techniques)
Background: Surgery for pediatric solid neoplasms is often complicated by local tumor invasion. Cardiac surgeons can provide expertise in the chest and facilitate potentially aggressive management of tumors invading vasculature, pericardiac, or diaphragmatic spaces. Here we present 4 complex cases. Methods: This descriptive retrospective chart review study included 4 surgical patients with locally invasive solid tumors. Results: Case 1: 16 × 15.5 × 11 cm right chest synovial sarcoma in a male patient status post–neoadjuvant chemoradiation. Imaging revealed invasion of the right-sided subclavian vein, subclavian artery, phrenic nerve, and vagus nerve. The surgical approach via hemi-clamshell allowed for R0 resection. Case 2: Resection of a 17.6 × 10.5 × 8.1 cm sclerosing epithelioid fibrosarcoma originating from the vertebral body but causing aortic arch, right and left pulmonary artery, tracheal, and esophageal displacement. The surgeons preserved nearly all thoracic anatomy despite extensive periaortic and posterior mediastinal dissection. Case 3: Synchronous removal of a 11.5 × 9 × 5.5 cm pleuropulmonary blastoma at the time of tetralogy of Fallot repair. Case 4: Resection of a 12 × 0.5 × 0.3 cm nonviable Wilms tumor traversing from the right renal vein to the level of the Eustachian valve. All patients were extubated in the operating room and had an uneventful hospital course, with length of stay ranging from 5 to 10 days. Conclusions: Pediatric patients may present with locally advanced heterogenous neoplasms. The added anatomic familiarity with the mediastinum, thoracic hilum, and great vessels in particular ensured safe resection in all cases. Thus, cardiothoracic surgery consultation is valuable when managing complex thoracic oncologic tumor resection.